2015
DOI: 10.1111/acv.12201
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds in the relationship between functional diversity and patch size for mammals in the Brazilian Atlantic Forest

Abstract: Patch size affects abundance and diversity of mammal species, but there is little information on threshold regarding this relationship or relating it to functional diversity. Therefore, we aimed with this study to (1) evaluate if the functional diversity of medium‐ and large‐sized mammal assemblages can be explained by patch size; (2) if this relationship is positive, evaluate whether it is linear (neutral hypothesis) or has critical thresholds (threshold hypothesis); (3) propose specific conservation strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 75 publications
3
58
0
6
Order By: Relevance
“…And in the same way that habitat fragmentation can improve some community metrics (such as beta-diversity), it may also have positive consequences for some functional metrics. For example, Magnago et al [11] found functional divergence to decrease with increasing patch size, whereas the majority of authors found an increase with patch size [9,28,32,33]. There are a number of reasons why these results may have been generated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And in the same way that habitat fragmentation can improve some community metrics (such as beta-diversity), it may also have positive consequences for some functional metrics. For example, Magnago et al [11] found functional divergence to decrease with increasing patch size, whereas the majority of authors found an increase with patch size [9,28,32,33]. There are a number of reasons why these results may have been generated.…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of functional diversity metrics can be seen in the landscape ecology literature, where a number of studies have employed these measures to better understand how landscape change affects communities and ecosystems [9][10][11]. Observed changes to functional diversity metrics are interpreted as direct evidence that rates of ecosystem processes are also affected.…”
Section: This Article Is Part Of the Topical Collection On Effects Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite not knowing whether (1) breeding performance has changed in the Sandveld following agricultural development and a changing prey base or (2) the differences in breeding productivity between the sites already occurred prior to agricultural transformation of the Sandveld, our findings support the notion that Verreaux's Eagles can maintain good breeding productivity in agriculturally transformed areas. However, there is likely to be a threshold of transformation tolerance whereby functional diversity and prey availability are not compromised (Magioli et al 2015). Land use and climate change are the 2 major pressures facing biodiversity loss globally.…”
Section: Discussionmentioning
confidence: 99%
“…PECB has high richness and diversity of mammal species (Brocardo et al 2012), being one the most preserved Atlantic Forest remnants, including some threatened species such as Brachyteles arachnoides, Tayassu pecari, Panthera onca and Speothos venaticus, and an important source area of mammals' ecological functions (Magioli et al 2015).…”
Section: Methodsmentioning
confidence: 99%